2019
DOI: 10.1186/s12885-018-5195-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis by deep sequencing of pancreatic juice from patients with pancreatic ductal adenocarcinoma

Abstract: BackgroundReliable methods are needed to identify patients with early-stage cancer or high-grade precancerous lesions in the pancreas. Analysis of pancreatic juice to detect somatic mutations could represent one such approach. Here we investigated the concordance between mutations found in the primary tumor and pancreatic juice from the same patient.MethodsAmplicon-based targeted deep sequencing was performed on samples from 21 patients with pancreatic ductal adenocarcinoma (PDAC) who had undergone Whipple’s o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…However, there is also evidence that at least a fraction of human PDACs can develop outside the PanIN-PDAC sequence paradigm [5][6][7]. Several studies have shown that Kras mutations can be detected at higher frequency in pancreatic juice and stool of patients with PDAC compared to normal patients and patients with benign pancreatic pathologies [8][9][10], making this disease potentially amenable to prevention or early interception.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also evidence that at least a fraction of human PDACs can develop outside the PanIN-PDAC sequence paradigm [5][6][7]. Several studies have shown that Kras mutations can be detected at higher frequency in pancreatic juice and stool of patients with PDAC compared to normal patients and patients with benign pancreatic pathologies [8][9][10], making this disease potentially amenable to prevention or early interception.…”
Section: Introductionmentioning
confidence: 99%
“…RAS mutations can potentially serve as good targets for immunotherapies since the mutations are usually in hotspot mutations and are common among cancer patients with various types of cancer (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). We have previously detected T cell reactivity against RAS hotspot driver mutations and identified the accompanying TCR from reactive TILs from 3 patients (17,52).…”
Section: Discussionmentioning
confidence: 99%
“…Author Manuscript Published OnlineFirst on June 24, 2021; DOI: 10.1158/1078-0432.CCR-21-0849 colon cancer express a RAS mutation (19)(20)(21)(23)(24)(25)(26)(27)(28). The human RAS super-family proteins (KRAS/NRAS/HRAS) have an identical amino acid sequence in positions 1 through 86 (20,25), and over 99% of all mutations in this gene family occur at positions 12, 13 or 61 (COSMIC database (29)) within the domains responsible for GTP dephosphorylation into GDP, resulting in constitutive activation of the RAS protein (20)(21)(22)(23)25,28,30).…”
Section: Introductionmentioning
confidence: 99%
“…This method has a reported sensitivity of up to 82% for the detection of KRAS mutation in PDAC patients [ 53 , 54 ], however, it is likely to have a lower specificity given the propensity for mucus to be generated by benign or malignant colorectal polyps which also frequently harbour KRAS mutation [ 24 ]. The development of more advanced KRAS mutant detection methods will also improve test sensitivity [ 55 ]. This is the case for droplet digital PCR [ 56 ], a method ideally suited to the detection of mutations existing in samples such as pancreatic secretions which contain low levels of nucleic acid and suffer from abundant protein contamination.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for droplet digital PCR [ 56 ], a method ideally suited to the detection of mutations existing in samples such as pancreatic secretions which contain low levels of nucleic acid and suffer from abundant protein contamination. Alternatively, incorporation of multiple genetic indicators such as panels of mutations, DNA methylation status [ 46 , 54 ] or simultaneous tumour marker assessment [ 55 ] could be used to improve sensitivity.…”
Section: Discussionmentioning
confidence: 99%